A novel method to produce potassium chromate from carbon ferrochrome - Hu, Guo-rong; Wang, Jia-liang; Peng, Zhong-dong; Du, Ke (Journal of Central South University, 2015)
The oxidizing roasting of carbon ferrochrome in the presence of potassium carbonate and air was investigated. The effects of reaction temperature, reaction time, ratio of alkali-to-ore were studied, together with a discussion of the thermodynamics and macro kinetics. It is observed that the reaction temperature and reaction time have significant influence on the roasting reaction. The reaction mechanism changes greatly as the temperature varies. A two-stage roasting process is favorable for the roasting reaction, and a recovery ratio of 96.51% is obtained through this two-stage roasting method. The chromium residue yielded from this method is quite little, only one third of the product. Moreover, the component of Fe in the residue is as high as 54.28%. Therefore, it can be easily recovered to produce sponge iron, realizing zero-emission of chromium residue.